Establishing a nutrition calculation model for catering food according to the influencing factors of energy and nutrient content in food processing - Li, Nan; Cong, Liangzi; Wang, Heng; Chen, Yamin; Liu, Zhaowei; Li, Mingliang; Yang, Dong; Li, Huzhong; Fang, Haiqin (Frontiers in Nutrition, 2024)
This study aimed to establish an accurate and efficient scientific calculation model for the nutritional composition of catering food to estimate energy and nutrient content of catering food. We constructed a scientific raw material classification database based on the Chinese food composition table by calculating the representative values of each food raw material type. Using China's common cooking methods, we cooked 150 dishes including grains, meat, poultry, fish, eggs, and vegetables and established a database showing the raw and cooked ratios of various food materials by calculating the ratio of raw to cooked and the China Total Diet Research database. The effects of various cooking methods on the nutritional composition of catering food were analyzed to determine correction factors for such methods on the nutritional components. Finally, we linked the raw material classification, raw and cooked ratio, and nutritional component correction factor databases to establish a model for calculating the nutritional components of catering food. The model was verified with nine representative Chinese dishes. Results revealed that the model was scientific, accurate, and efficient, thereby promising in facilitating the accurate calculation and correct labeling of nutritional components in catering food.